Answer:
The correct option is D
Step-by-step explanation:
Given the function:
![f(x)=x^2-5x+6](https://img.qammunity.org/2023/formulas/mathematics/college/ij2q5jc1vo3dhycx8lnxpenqjnemozvgd0.png)
This may be written as:
![y=x^2-5x+6](https://img.qammunity.org/2023/formulas/mathematics/college/9tsbet8he4df53fhzn1q82fg8lr7nad0sd.png)
For x = -5, -4, -3, -2, -1, 0, 1, 2, 3, 4, 5
we need to find the corresponding values for y.
For x = -5
y = (-5)^2 - 5(-5) + 6
= 56
For x = -4
y = (-4)^2 - 5(-4) + 6
= 42
For x = -3
y = (-3)^2 - 5(-3) + 6
= 30
For x = -2
y = (-3)^2 - 5(-2) + 6
= 20
For x = -1
y = (-1)^2 - 5(-1) + 6
= 12
For x = 0
y = (0)^2 - 5(0) + 6
= 6
For x = 1
y = (1)^2 - 5(1) + 6
= 2
For x = 2
y = (2)^2 - 5(2) + 6
= 0
For x = 3
y = 3^2 - 5(3) + 6
= 0
For x = 4
y = 4^2 - 5(4) + 6
= 2
For x = 5
y = 5^2 - 5(5) + 6
= 6
By inspection, we see that the correct option is D